Genetic loss of the dopamine transporter significantly impacts behavioral and molecular responses to sub-chronic stress in mice - Petri, Avelina; Sullivan, Abigail; Allen, Kristen; Sachs, Benjamin D. (Frontiers in Molecular Neuroscience, 2024)
Dopaminergic neurotransmission has emerged as a critical determinant of stress susceptibility and resilience. Although the dopamine transporter (DAT) is known to play a key role in maintaining dopamine (DA) homeostasis, its importance for the regulation of stress susceptibility remains largely unknown. Indeed, while numerous studies have examined the neurochemical and behavioral consequences of genetic loss of DAT, very few have compared responses to stress in wild-type and DATknockout (KO) animals. The current study compared the responses of male and female WT and DAT-KO mice to a model of sub-chronic stress. Our results reveal that DAT-KO mice are resistant to stressinduced increases in the latency to enter the light chamber of the light-dark emergence test and demonstrate that DAT-KO mice exhibit baseline reductions in forced swim test immobility and grooming time in the splash test of grooming behavior. In addition to these behavioral changes, our results highlight the importance of sex and dopaminergic neurotransmission on stress-induced changes in the expression and phosphorylation of several signal transduction molecules in the nucleus accumbens that have previously been implicated in the regulation of stress susceptibility, including ERK, GSK3β, and ΔFosB. Overall, these results provide further evidence of the importance of dopaminergic neurotransmission in regulating stress susceptibility and suggest that genetic loss of DAT prevents stress-induced increases in anxiety-like behavior.